Land Disputes and Settlement at the Notary - Aslan Noor; Anik Istiqamah; Nurfaridah Nurfaridah; Ardisia Rahma Susetyo; Andhika Wijaya Pratama (Jurnal Info Sains : Informatika dan Sains, 2023)
This research aims to explore the role of notaries in resolving land disputes as an effort to realize legal certainty and protect the rights of the parties involved. Land disputes are complex problems that often involve various parties with diverse interests. The research method used is empirical law to illustrate how notaries can be effective mediators in resolving land disputes. The research results show that the role of notaries in the context of land disputes is very important to create legal certainty and prevent conflicts. Notaries not only act as makers of land deeds, but also as legal advisors, mediators and expert witnesses in court. By carefully examining documents, providing legal advice, and playing a role in the dispute resolution process, notaries can help reduce the risk of disputes, provide effective resolution pathways, and add additional strength to evidence in court. The holistic existence of a notary helps create a stable and fair legal environment regarding land ownership in society.